PENYELESAIAN KREDIT MACET TANPA JAMINAN PADA KOPERASI - Putra Mahardika, I Gusti Ngurah Putu; R, Ibrahim (Kertha Semaya : Journal Ilmu Hukum, 2013)
Legal protection of consumers of LPG user perspective in the review of the consumer protection law. The problem is how the legal protection of consumers of the dangers of exploding LPG LPG regulator? And Do sanctions for businesses if the explosion in LPG gas regulator? Writing method using normative methods that are descriptive. Results in the review of the Law No.. 8 of 1999 on consumer protection is a legal research regarding the enforcement or implementation of normative law in action on any specific legal events happening in the community.
Keywords: Legal Protection, Perspective, Consumer, LPG Gas